Non-precious transition metal based electrocatalysts for vanadium redox flow batteries: Rational design and perspectives - Huang, Rongjiao; Wang, Jue; Liu, Suqin; Yang, Yuliang; Deng, Weiwen; Su, Yuke (Journal of power sources, 2021)
The vanadium redox flow battery (VRFB) is promising for large-scale energy storage, but commercial electrodes, such as graphite felt (GF), suffer from poor electrochemical activity caused by sluggish kinetics and high polarization, leading to a need for high performance and cost-effective electrocatalysts. Non-precious transition metal based materials show great promise as electrocatalysts for VRFB due to their activity and low cost. However, limited exposed active sites and their low intrinsic conductivity, in addition to the unsettled relationship between the structure and performance, remain to be solved. To clarify rational design principles and strategies for obtaining high-performance non-precious transition metal based electrocatalysts in VRFB, this review summarizes their recent advances, primarily focusing on defect engineering, engineering of hybrid materials, and hierarchical porous structure designing. In addition, we propose the challenges and prospects of non-precious transition metal based materials in VRFB, which should inspire insight into designing and optimizing non-precious transition metal based electrocatalysts in VRFB, as well as promoting the commercial application of VRFB. [Display omitted] •Insightful review on non-precious transition metal based electrocatalysts for VRFB.•Strategies to improve the electrochemical performance are summarized.•The relationship between designing strategies and performance is analyzed.•Challenges and perspectives of this kind of electrocatalysts in VRFB are proposed.